(untitled) (Faridpur Medical College Journal, 2026)
Background: Over the last two decades, contamination of blood product with pathogenic bacteria has become a major concern in blood transfusion practice, being recognized as the second leading cause of transfusion-related fatalities after ABO incompatibility. Platelet transfusions pose a higher risk of bacterial sepsis than red cell concentrates due to their storage conditions at standard temperature, suspension in plasma, and storage bags allowing oxygen diffusion. To detect incidence and type of micro bacterial contamination of platelet concentrates (PCs) stored at standard temperature. Materials & Methods: This cross-sectional study was implemented at a tertiary care university hospital in Bangladesh involving 44 healthy blood donors. With all available aseptic precautions, each donor provided 450 ml of blood into a CPDA-1 anticoagulant-containing blood bag system. Collected whole blood was promptly cooled to 20–24°C within two hours and then processed for separation into components. Platelet concentrates were obtained through centrifugation. Each Platelet concentrate was maintained at standard temperature which is 20°C to 24°C with consistent, mild agitation throughout the 5-day storage period. Five ml samples were collected from each platelet concentrate bag on day 0, 3, 5 and culture sensitivity was done in the Dept of Microbiology. Statistical analysis was conducted using SPSS-22 software. Results: Most (63.6%) of the blood donor participants’ age belonged to 21-30 years and the male female proportion was almost 3.9:1. The most common blood group (38.6%) among blood donors was B (+ve). Samples collected from each platelet conc. bag on day 0, 3 and 5 showed no change in physical appearance or color of the component, and no bacteremia was detected in any of the samples. Conclusion: No bacterial contamination was observed in this study, and it reflects the institute’s best efforts to adhere to the required practice guideline for a satisfactory storage of PC at 20°C to 24°C. Faridpur Med. Coll. J. 2026;21(2): 44-50